Construction of a N-CDs/AuNCs@ZIF-8-assisted ratiometric fluorescent nanosensor for glyphosate detection in edible and medicinal malt - Doudou Lei; Lingling Li; Pengyue Song; QingBin Xu; Lihua Huang; Xiao Ma; Lidong Zhou; Weijun Kong (Food Chemistry: X)
Glyphosate (Gly) is a widely-used herbicide in food production, while, the residue of which due to the long-term and excessive overspray poses serious threats to public health. The development of reliable methods for its sensitive detection is of great urgency. In this study, a novel ratiometric fluorescent nanosensor by encapsulating N-doped carbon dots (N-CDs) and gold nanoclusters (AuNCs) in zeolitic imidazole framework-8 (ZIF-8) as the dual-emissive fluorescence probes at 410 and 650 nm, respectively, was constructed for Gly detection. Due to the adsorption property of ZIF-8, the N-CDs/AuNCs@ZIF-8 nanoprobes accumulated Cu2+ to quench the red fluorescence of AuNCs, and the blue fluorescence of N-CDs was stable. While thiocholine, a product of acetylthiocholine, hydrolyzed by acetylcholinesterase could coordinate with Cu2+, resulting in significant fluorescence recovery of AuNCs. This phenomenon was utilized for the quantitation of Gly, due to its inhibitory effect on acetylcholinesterase activity. By calculating the fluorescence intensity ratio (I650/I410), Gly in real sample could be accurately determined in a concentration range of 2–100 ng/mL with a limit of detection of 1.92 ng/mL because of the anti-interference and the self-correction ability of the two fluorescence signals. The N-CDs/AuNCs@ZIF-8 nanoprobes-assisted ratiometric fluorescent nanosensor exhibited unique merits of rapid construction, simple operation, high specificity, and good accuracy for Gly in edible and medicinal malt samples with recoveries of 93.7–108.2 %. This study presents a multiple tool for the versatile sensing of trace pesticides in more food matrices, which can be extended to a full range of environmental and food safety applications.